Psychological Impact of the COVID-19 Pandemic among Frontline Health Workers in Gandaki Province, Nepal - Thapa, Nirupa; Shrestha, Nisha; Ghimire, Gita Devi (Journal of Nursing and Health Sciences Nepal, 2023)
Introduction: Coronavirus disease (COVID-19) has envisioned great fear in people including health workers who faced various problems such as work overload, long duty hours, fear of getting infected, discrimination, and stigmatization. The aim of this study was to identify psychological impact of COVID-19 among frontline health workers and identify the associated factors for post-traumatic stress disorders. Methods: A cross-sectional descriptive research design was used to collect data using web-based questionnaire from 235 purposively selected health workers working in hospitals of Gandaki Province. Descriptive data were analyzed using mean, frequency and percentage; and Chi-square test to find association between variables. t-test and ANOVA were used to determine factors for PTSD among health professionals. Results: The results indicated that 51.5% of health workers had psychological impact of clinical concern. Among them, 35.3% had likely presence of PTSD and 28.5% had severe psychological impact who can show impact even 10 years after the event. There were differences in experiencing traumatic stress differentiated by age, gender and profession where males had higher traumatic stress for all dimensions than females, and doctors had higher stress than nurses. Moreover, having a family member with a chronic disease, working in a higher level health facility with either intermediate or below educational level or higher educational level master’s, and being under medication for mental illness was more stressful. Health workers working overtime, facing any stigma, and having a change in their regular jobs were more stressed. Conclusions: The prevalence rates of psychological impact reveal a worrying view of mental health challenges among Nepalese frontline health workers. Hence, the best possible care with psychological support and first aid should be provided to health workers.